2021
DOI: 10.3855/jidc.12103
|View full text |Cite
|
Sign up to set email alerts
|

Two different clones of Candida pelliculosa bloodstream infection in a tertiary neonatal intensive care unit

Abstract: Introduction: Fungemia in preterm infants results in high mortality and morbidity. The genotypes, drug susceptibilities of Candida pelliculosa strains, and clinical features of two outbreaks of neonatal candidemia caused by C. pelliculosa were analyzed, in order to provide evidence for the outbreaks and characteristics of C. pelliculosa neonatal candidemia. Methodology: The strains were genotyped by pulsed-field gel electrophoresis to investigate their genetic relatedness. The broth microdilution method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…New lines of studies, however, have revealed its clinical importance and have implicated this species in a wide range of fungal infections, such as keratitis, meningitis, and candidemia, in immunocompromised and neonatal patients (Neumeister et al, 1992;Park et al, 2008;Ratcliffe et al, 2011). Moreover, this species has been associated with a relatively high mortality rate (41.2%) (Pasqualotto et al, 2005), and numerous studies have found this species as a cause of outbreaks (Kalenic et al, 2001;Kalkanci et al, 2010;Jung et al, 2018), especially among neonates (da Silva et al, 2013;Lin et al, 2013;Yang et al, 2021). While molecular tools failed to be identified from the hands of healthcare workers, they have revealed that W. anomalus isolates obtained from the outbreaks are genetically related, and importantly, the application of strict infection control and hand hygiene practices has resulted in eradication of such infections in hospitals with ongoing outbreaks due to W. anomalus (Pasqualotto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…New lines of studies, however, have revealed its clinical importance and have implicated this species in a wide range of fungal infections, such as keratitis, meningitis, and candidemia, in immunocompromised and neonatal patients (Neumeister et al, 1992;Park et al, 2008;Ratcliffe et al, 2011). Moreover, this species has been associated with a relatively high mortality rate (41.2%) (Pasqualotto et al, 2005), and numerous studies have found this species as a cause of outbreaks (Kalenic et al, 2001;Kalkanci et al, 2010;Jung et al, 2018), especially among neonates (da Silva et al, 2013;Lin et al, 2013;Yang et al, 2021). While molecular tools failed to be identified from the hands of healthcare workers, they have revealed that W. anomalus isolates obtained from the outbreaks are genetically related, and importantly, the application of strict infection control and hand hygiene practices has resulted in eradication of such infections in hospitals with ongoing outbreaks due to W. anomalus (Pasqualotto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 243 articles from PubMed and Scopus were screened. Finally, 36 met the present study’s inclusion criteria [ 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These 36 studies involved 170 patients in total.…”
Section: Resultsmentioning
confidence: 99%
“…However, an increasing number of reports of human infections by W. anomalus have emerged, suggesting that this microorganism is an emerging pathogen. For example, there are reports of clonal outbreaks of invasive fungal disease, more commonly fungemia [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 211 cases, 154 cases (73%) were pediatrics, mostly including neonates. Twelve articles reported on nosocomial infections causing outbreaks [ 2 , 8 , 12 , 23 , 25 , 26 , 30 , 43 , 46 , 48 , 49 , 51 ]. Fungemia was reported in 199 cases (94%), and four cases were eye involvement such as endophthalmitis [ 11 , 47 ] or keratitis [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%